PENGARUH KUALITAS PELAYANAN BAGIAN ADMINISTRASI DAN AKADEMIK TERHADAP KEPUASAN MAHASISWA DI STIE MANDALA JEMBER - Amien Pudjanarso (RELASI : JURNAL EKONOMI, 2017)
This research aims to know the effect of the quality of service that includes physical evidence,responsiveness,reliability,assurance,and empathy to wards the satisfaction of the student in STIE Mandala Jember.This type of correlational study aims to find the effect of simultaneous,partial as well as the most dominant variable.The population in this research as many as239 college students and research on a sample of 40 students. Data collected with the question form and analyzed by Multiple Linear regression analysis.Based on the results of the analysis are simultaneously influence is evidenced by the hypothesis test is done,the F test the value of F=23.151,while the value of F table=2.49.Being partially showed variable  physical evidence and the low responsiveness of services provent ot count lower or less than t table ie 1.69092. And proved to be the most dominant variable empathy with t count most not ably 2,581.That is a need to increase the quality of services, the better implementation of service quality dimensions,the higher the student satisfaction, and viceversa.